Computer-Assisted Teaching and Learning of Electronic Circuit on Student’s Motivation, Achievement and Cognitive Load - Omar, Nurul Ihsaniah; Ibrahim, Abu Bakar; Abdul Kadi, Akmanisah (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2023)
This paper aims to see the effectiveness of computerized simulation with electronic circuits on students' motivation, achievement and cognitive load. This study uses mechanical electronic circuit simulation as a teaching aid and facilitator for students studying Design and Technology subjects. The objective of this study is to evaluate the effect of using simulation on students' motivation, achievement and cognitive load. This study is also to discuss the development of Simulation and laboratory worksheets for LiveWire software that will be developed for the Design & Technology subject for second-year students at the high school level. The method presented using LiveWire is a systematic work step in exploring the use of simulation for electronic circuits. This electronic circuit simulation is able to give students the ability to read, interpret and transfer wiring circuits to schematic circuits. This LiveWire simulation is also suitable and able to improve the construction of meaningful knowledge for students. Assessment is done through post-tests, Instructional Material Motivation Scale (IMMS) questions and the NASA Task Load Index cognitive load test. The results of this study show that electronic circuit simulation has a positive effect on students' motivation, achievement and cognitive load.